Penyuluhan Kohabitasi Dalam Perspektif Islam Dan Budaya Lokal Untuk Meningkatkan Pariwisata Berkelanjutan Di Desa Setanggor - Muaidy Yasin; Wahyunadi; Suheflihusnaini Ashady; Dina Amalya Putri; Aryadi Almau Dudy; Dewi Riskiani (Universitas Mataram, 2026)
Counseling on cohabitation from the perspectives of Islam and local culture plays an important role in supporting sustainable tourism in Setanggor Village. This activity was carried out through a legal counseling method involving village officials, community leaders, religious leaders, traditional leaders, and tourism stakeholders within the community. The counseling was conducted using persuasive and participatory approaches to enhance public understanding of the importance of maintaining religious norms, customs, and local cultural identity amid the development of modern tourism. The results showed that the counseling method was quite effective in building public legal awareness, enabling the community to maintain a balance between tourism development and the preservation of Islamic values and the local culture of the Sasak community.